Short chain fatty acids prime colorectal cancer cells to activate antitumor immunity - Mowat, Courtney; Dhatt, Jasmine; Bhatti, Ilsa; Hamie, Angela; Baker, Kristi (Frontiers in Immunology, 2023)
Introduction. Colorectal cancer (CRC) is a leading cause of death worldwide, and its growth can either be promoted or inhibited by the metabolic activities of intestinal microbiota. Short chain fatty acids (SCFAs) are microbial metabolites with potent immunoregulatory properties yet there is a poor understanding of how they directly regulate immune modulating pathways within the CRC cells. Methods. We used engineered CRC cell lines, primary organoid cultures, orthotopic in vivo models, and patient CRC samples to investigate how SCFA treatment of CRC cells regulates their ability to activate CD8+ T cells. Results. CRC cells treated with SCFAs induced much greater activation of CD8+ T cells than untreated CRC cells. CRCs exhibiting microsatellite instability (MSI) due to inactivation of DNA mismatch repair were much more sensitive to SCFAs and induced much greater CD8+ T cell activation than chromosomally instable (CIN) CRCs with intact DNA repair, indicating a subtype-dependent response to SCFAs. This was due to SCFA-induced DNA damage that triggered upregulation of chemokine, MHCI, and antigen processing or presenting genes. This response was further potentiated by a positive feedback loop between the stimulated CRC cells and activated CD8+ T cells in the tumor microenvironment. The initiating mechanism in the CRCs was inhibition of histone deacetylation by the SCFAs that triggered genetic instability and led to an overall upregulation of genes associated with SCFA signaling and chromatin regulation. Similar gene expression patterns were found in human MSI CRC samples and in orthotopically grown MSI CRCs independent of the amount of SCFA producing bacteria in the intestine. Discussion. MSI CRCs are widely known to be more immunogenic than CIN CRCs and have a much better prognosis. Our findings indicate that a greater sensitivity to microbially produced SCFAs contributes to the successful activation of CD8+ T cells by MSI CRCs, thereby identifying a mechanism that could be therapeutically targeted to improve antitumor immunity in CIN CRCs.